Pengaruh Layanan Home Visit dan Partisipasi Orang Tua Terhadap Hasil Belajar Matematika Siswa Sekolah Dasar di Tengah Pandemi Covid-19 - Lailatuz Zuhro; Mufidatus Sholikhah; Valensiana Vortunata Ari Ustoyo; Siti Lailiyah (JRPM (Jurnal Review Pembelajaran Matematika), 2021)
During the COVID-19 pandemic, online learning (online) has been continuing. The lack of online learning is a home visit service emerged to monitor students' learning. Apart from teachers, parental participation is very important in determining children's learning achievement. This study aims to describe the relationship between home visits services and parental participation in mathematics learning outcomes for grade 2 elementary school. The method in this study is quantitative research. This study involved 32 third-grade students at Al-Aqsa Islamic elementary school in Sidoarjo as research subjects. The research instrument consisted of a questionnaire of home visits and parental participation in learning mathematics. Data collection using a home visit questionnaire and parental participation and documentation of mathematics learning outcomes. The analysis data with a correlational approach using multiple linear regression analysis. The results of this study indicate the home visit service, parents, and mathematics learning outcomes are included in the very goods category. This means that home visit services can improve children's mathematics learning outcomes.